Push-pull π-conjugated heterocyclic systems and organometallic complexes: design, synthesis and application for second-order nonlinear optics (NLO) and for dye-sensitized solar cells (DSSCs) - Fernandes, Sara Sofia Marques (2017)
Tese de Doutoramento em Ciências (Especialidade em Química)